Jangkaan impak pembinaan empangan hidroelektrik terhadap komuniti Orang Asli - Sarmila Md. Sum, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Electricity demand in Malaysia continues to increase due to population growth, expansion of industrial and commercial development. The existing electricity supply cannot fulfill future demands. Therefore, an alternate power supply should be identified. Beside coal, gas and nuclear power, hydroelectric is another ideal means to fulfill the country’s electricity demand effectively because it is renewable, cheap and environment-friendly. Tekai river in Jerantut, Pahang, is an appropriate area for the construction of a hydroelectric dam. Briefing and dialogue series between energy’s company and the indigenous community of (Orang Asli) at Tekai river, and a field trip to Lake Kenyir Hydroelectric Dam have been held. This study aims to explore the Orang Asli community expectation with regard to the potential impacts of hydroelectric dam construction on their livelihood. This research is based on community livelihood model that examines the interconnection of the Orang Asli community with the surrounding natural environment. A qualitative approach is used by performing in-depth interviews with 20 informants. The data analysis is based on a verbatim transcription of the interviews and performed in accordance with emerging themes. Results indicate the community realized that the natural forests and river used for food sources and income have been exploited. They believe this dam will not entirely benefited them in the future; instead, it will be an inconvenience because they cannot arbitrarily enter the dam area. In addition, they cannot adapt for survival due to the lack of forest areas that provide resources. Hence, a few suggestions to improve Orang Asli livelihood by improving education, attitude, minds and skills, strengthening economic empowerment, upgrade infrastructure and basic facilities and implementing youth capacity building programs.